Assessing Variability in In-Hospital Complication Rates Between Surgical Services for Patients Undergoing Posterior Cervical Decompression and Fusion. Issue 3 (1st February 2019) - Snyder, Daniel J.; Neifert, Sean N.; Gal, Jonathan S.; Deutsch, Brian C.; Rothrock, Robert; Hunter, Samuel; Caridi, John M.
Abstract : Study Design: A retrospective study was performed including all patients who underwent posterior cervical decompression and fusion (PCDF) by an orthopedic or neurological surgeon at a single institution between January 1, 2006 and November 30, 2016, and all patients who underwent PCDF by a spine surgeon in the National Surgical Quality Improvement Project database between 2007 and 2015. In-hospital complications were compared between surgical specialties. Objective: The goal of this study was to determine if in-hospital complication rates differ significantly between surgical services for PCDF patients. Summary of Background Data: Orthopedic and neurological surgeons commonly perform PCDF, and differences in surgical opinion and management have been cited between these two specialties in recent literature. This represents a variable that should be evaluated. Methods: Cases were preliminarily identified by CPT code and confirmed using the ICD-9 code 81.03 or ICD-10 code M43.22. Cases were separated based on if the primary surgeon was an orthopedic surgeon or a neurological surgeon. The primary outcome variable was in-hospital complication rates; cohorts were compared using bivariate and multivariate analysis. Results: A total of 1221 patients at a single institution and 11, 116 patients within the National Surgical Quality Improvement Project database underwent PCDF. Patients in the orthopedic surgery service had a higher proportion of bleeding requiring transfusion in both the institutional sample (14.5% vs. 9.08%, P  = 0.003) and national sample (11.16% vs. 6.18%, P  < 0.0001). In the national sample, orthopedic surgeons were 1.66 times as likely to encounter an in-hospital complication than neurological surgeons (95% CI: 1.44–1.91, P  < 0.0001). Conclusion: When examining a large institutional sample and an even larger national sample, this study found that orthopedic surgeons were more likely to encounter perioperative bleeding requiring transfusion than neurological surgeons. When in-hospital complications were considered as a whole, in the national sample, orthopedic surgeons are more likely to encounter in-hospital complications than neurological surgeons when performing PCDF. Level of Evidence: 3 Abstract : Orthopedic and neurological surgeons commonly perform PCDF; differences in surgical opinion and management have been cited between these two specialties. When examining an institutional (n = 1221) and national sample (n = 11, 116), orthopedic surgeons were more likely to have in-hospital complications, in particular perioperative bleeding requiring transfusion, than neurological surgeons when performing PCDF.